Hedgehog-GLI mediated control of renal formation and malformation - Greenberg, Dina; D’Cruz, Robert; Lacanlale, Jon L.; Rowan, Christopher J.; Rosenblum, Norman D. (Frontiers in Nephrology, 2023)
CAKUT is the leading cause of end-stage kidney disease in children and comprises a broad spectrum of phenotypic abnormalities in kidney and ureter development. Molecular mechanisms underlying the pathogenesis of CAKUT have been elucidated in genetic models, predominantly in the mouse, a paradigm for human renal development. Hedgehog (Hh) signaling is critical to normal embryogenesis, including kidney development. Hh signaling mediates the physiological development of the ureter and stroma and has adverse pathophysiological effects on the metanephric mesenchyme, ureteric, and nephrogenic lineages. Further, disruption of Hh signaling is causative of numerous human developmental disorders associated with renal malformation; Pallister-Hall Syndrome (PHS) is characterized by a diverse spectrum of malformations including CAKUT and caused by truncating variants in the middle-third of the Hh signaling effector GLI3. Here, we outline the roles of Hh signaling in regulating murine kidney development, and review human variants in Hh signaling genes in patients with renal malformation.